Researching Of Ranking Handball Referees' Job Satisfaction Levels In Terms Of Some Parameters, - Gündoğdu, C., Yücel, A. S., Küçük V., Karataş, Ö., (My University, 2012)
This research has been conducted in order to determine the job satisfaction levels of the ranking referees in terms of some parameters (sex, age, marital status, income states, other profession, and refereeing period). This research is a descriptive study towards the review of job satisfaction levels of Handball ranking referees. Referees take charge in 2010-11 season in Turkish leagues constitute the population of the research. Accordingly 107 Ranking referees under Turkish Handball Federation constitute the sample of the research. SPSS package program was used for the statistical analyses. Measuring tool is constituted of two sections. In first section a test directed towards to determine the demographical features of the referees while in second section “Minnesota job satisfaction scale” was used. Validity and reliability studies were made (cronbach alpha =0.70). It was determined that statistically there is not a significant gap between the job satisfaction levels of the referees according to their sex, marital status, ranking position, refereeing periods and income status; and statistically there is a significant gap between their job satisfaction levels according to their ages. Increase of job satisfaction with the increase of age, increase of the experience, awards, rise of refereeing ranking and coalescence with the job are considered to be the factors for the existence of such difference. Income levels of the majority of the referees are seen to be at intermediate level.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Handball; Referee; Job satisfaction; Variant; Ranking